2011
DOI: 10.1121/1.3655893
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric glottal jet deflection: Differences of two- and three-dimensional models

Abstract: Flow is studied through a channel with an oscillating orifice mimicking the motion of the glottal-gap during phonation. Simulations with prescribed flow and wall-motion are carried out for different orifice geometries, a 2D slit-like and a 3D lens-like one. Although the jet emerges from a symmetric orifice a significant deflection occurs in case of the slit-like geometry, contrary to the 3D lens-like one. The results demonstrate the dependency of jet entrainment and vortex dynamics on the orifice geometry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 9 publications
4
28
0
Order By: Relevance
“…This conclusion is also consistent with the very recent work of Mattheus and Br€ ucker (2011) which investigated the differences of asymmetric jet deflection in 2D and 3D models. In this work, the authors found that 3D glottal jets differ from the 2D jets due to the presence of the axis-switching phenomenon and smaller deflection angles.…”
Section: B Glottal Jet Evolutionsupporting
confidence: 92%
See 2 more Smart Citations
“…This conclusion is also consistent with the very recent work of Mattheus and Br€ ucker (2011) which investigated the differences of asymmetric jet deflection in 2D and 3D models. In this work, the authors found that 3D glottal jets differ from the 2D jets due to the presence of the axis-switching phenomenon and smaller deflection angles.…”
Section: B Glottal Jet Evolutionsupporting
confidence: 92%
“…Characteristic features of phonation, including glottal jet evolution, waviness in glottal jet, mucosal wave type VF vibration and 1:1 entrainment of principal modes of vibrations have been discussed in detail. The evolution pattern of glottal jet provides support to the notion that (Zheng et al, 2011a;Mattheus and Br€ ucker, 2011) the glottal flow asymmetry is driven primarily by the postglottal vortex dynamics.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The experiments were performed by using the geometry of the rectangular glottal gap as the base, which is moving at the end of the motion cycle in the reference case to a full closure and in the leaky case leaving some gaps at both ends of the model. Mattheus and Brücker (2011) showed that such a rectangular glottal gap (slit-like gap) produces vortex trains with rod-like structures that are mostly aligned in lengthwise direction of the folds, Fig. 12.…”
Section: Hg(+) Hg(−)mentioning
confidence: 99%
“…These include studies with fixed vocal folds (e.g. [12,13,14,15]), forced vocal fold oscillation [16,17,6,18,19,20,21,22,23] and models with the airflow fully coupled to elastic tissue oscillations [24,25,26,27,28,29,30]. Only a few of these computational studies [24,12,14,15,22] solve the flow field in 3D, and most of them on a static geometry.…”
Section: Previous Work In the Fieldmentioning
confidence: 99%